Kurikulum Pendidikan Islam: Tantangan Dan Peluang Di Tengah Globalisasi - Alfarisi, Salman; Bancin, M Khairul Sahdan; Nasution, M Riyansyah (Journal of Sustainable Education, 2025)
This study aims to thoroughly examine the challenges and opportunities faced by the Islamic education curriculum in the context of the ever-evolving globalization. Globalization has brought significant changes across various aspects of life, including the field of education, which demands the Islamic education curriculum to transform in order to remain relevant to current developments without losing the essence of Islamic teachings. The primary focus of this study is to identify both external and internal factors that influence the Islamic education curriculum and to formulate adaptive strategies that can be applied in its development. This research adopts a qualitative approach using library research and content analysis methods on curriculum documents, academic literature, national education policies, and the perspectives of Islamic education experts. Data were collected from various relevant primary and secondary sources and analyzed descriptively and critically to gain a comprehensive understanding of the issues discussed. The results show that the Islamic education curriculum faces several significant challenges in the era of globalization, including the dominance of foreign cultural values, the imbalance between religious and secular sciences, and limited innovation in teaching methods. Nevertheless, globalization also presents great opportunities for curriculum enhancement through the integration of educational technology, international collaboration among Islamic institutions, and the development of a character-based and globally competent curriculum.